Potential of Splitting Skin as Raw Material for Skin Crackers with Different Concentrations and Soaking Time in Vinegar - Pebrianto, Eko; Novia, Deni; Vebriyanti, Ely (Jurnal Peternakan, 2025)
ABSTRACT. Tannery solid waste, such as split skin residue, still contains lime, which is alkaline in nature, so it needs to be neutralized by adding vinegar. This research aimed to determine the best concentration and duration of skin immersion in acidic vinegar for water content, pH, texture, calcium content, and organoleptic splitting skin. This used an experimental method with a completely randomized design (CRD) with a 3 x 3 factorial pattern with three replications. Factor A (acetic acid concentration) consists of A1: 0%, A2: 3%, A3: 6%. Factor B (length of soaking) consists of B1: 8 hours, B2: 16 hours, B3: 24 hours. The variables observed were moisture content, pH, texture, calcium content, and split skin sensory. The results showed a significant interaction (P<0.05) between the concentration of acetic acid and the length of soaking on sensory skin color splitting. Still, there was no interaction (P>0.05) between the concentration of vinegar acid and the soaking time on water content, pH, texture, calcium content, and sensory aroma. From the research results, it can be concluded that the vinegar acid concentration of 3% and soaking time of 24 hours give optimal results with a moisture content of 46.12%, pH 7.33, texture 49.30 joules, calcium content 0.21%, sensory color 2.80 (white brownish) and sensory aroma 2.80 (no acid).